PENGARUH KEBIJAKAN LIBERALISASI PERDAGANGAN TERHADAP PERUBAHAN EKSPOR DAN IMPOR DI INDONESIA - Jamal Nasir Baso (Universitas Halu Oleo, 2017)
This study aims to determine the effect of trade liberalization policies on changes in exports and imports in Indonesia during the period 1996-2007. The type of data used is secondary data. The analysis tool uses Simple Linear Regression. Based on the results of the discussion between export and export taxes, R results are 0.787 while the contribution is R2 = 0.619 or 61.9 percent. Based on the t-test partially the export tax (X) has a significant effect on exports (Y) (t = 4.031> t table 1,812) and significance = 0.002 < Î± = 0.05 so reject H0 accept H1. While the results of the analysis between import duties and imports are obtained in the form of R amounting to 0.812 while the contribution of import duty and import is R2 = 0.673 or 67.3 percent. Based on the t-test partially the import duty (X) has a significant effect on the import variable (Y) (t stat = 4,541> t table = 1,812) and significance = 0.001 < Î± = 0.05, then reject H0 accept H1. Based on the results of the analysis it can be concluded that the export tax has a significant effect on exports and also the import duty has a significant effect on imports. So that in this case the policy of trade liberalization through export taxes and import duties significantly affected the development of exports and imports.